2020
DOI: 10.1016/j.fuproc.2020.106402
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemical conversion of agricultural wastes applying different reforming temperatures

Abstract: Link to publication on Research at Birmingham portal General rightsUnless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law.• Users may freely distribute the URL that is used to identify this publication.• Users may download and/or print one copy of the publication from the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 75 publications
1
23
0
Order By: Relevance
“…Brazilian Journal of Development, Curitiba, v.7, n.9, p. 89356-89381 sep. 2021 Sugarcane, given the large number of reports, proves to be an agronomic crop with great potential for the development of bioproducts (Bernardino et al 2018;Ullah et al 2019;Solorzano-Chavez et al 2019;Grewal and al. Khare 2018;Cervi et al 2021;Ponte et al 2019;Karimi et al 2018;Akond and Lynam 2020;Almeida et al 2017;Bezerra et al 2020;Coimbra et al 2021;Cortes et al 2020;da Silva et al 2020a;David et al 2019;Debernardi-Vázquez et al 2020;Gama et al 2019;Gomes et al 2016;Roldán et al 2017;Rulli et al 2019;Santos et al 2020 ) (Table 3). Several successful examples are reported, mainly in Asian countries.…”
Section: Culture Residue Bioproduct/bioinput and Process Referencementioning
confidence: 99%
“…Brazilian Journal of Development, Curitiba, v.7, n.9, p. 89356-89381 sep. 2021 Sugarcane, given the large number of reports, proves to be an agronomic crop with great potential for the development of bioproducts (Bernardino et al 2018;Ullah et al 2019;Solorzano-Chavez et al 2019;Grewal and al. Khare 2018;Cervi et al 2021;Ponte et al 2019;Karimi et al 2018;Akond and Lynam 2020;Almeida et al 2017;Bezerra et al 2020;Coimbra et al 2021;Cortes et al 2020;da Silva et al 2020a;David et al 2019;Debernardi-Vázquez et al 2020;Gama et al 2019;Gomes et al 2016;Roldán et al 2017;Rulli et al 2019;Santos et al 2020 ) (Table 3). Several successful examples are reported, mainly in Asian countries.…”
Section: Culture Residue Bioproduct/bioinput and Process Referencementioning
confidence: 99%
“…It has also been proved that intermediate pyrolysis of rice straw wastes proved to offset carbon dioxide than the rest of types [32]. Other intermediate pyrolysis studies on wastes such as organic fraction of municipal solid wastes [12], sugarcane bagasse [127], sugarcane bagasse and oat hulls [128], chicken manure for fertilizer and heat production [5], wheat husk [27], waste tires [129], and Bambara groundnut shells [24] have appreciated the advantages of intermediate pyrolysis. ese good results indicate the effectiveness of intermediate pyrolysis on the conversion of wastes when compared to current common technologies.…”
Section: Intermediate Pyrolysis As the Appropriatementioning
confidence: 99%
“…However, it should also be noted that increasing the reforming temperatures promotes cracking reactions to produce higher yields of syngas at the expense of liquids [46]. Santos et al [22] reported that the bio-oil yields of sugarcane bagasse and oat hulls are improved by running the TCR system at lower reforming temperatures (500, 600, and 700°C) which reduce the enhanced cracking of organic vapors. Furthermore, TCR makes a better separation between the water phase and organic phase of the pyrolysis liquid, and this is the reason why the HHV of TCR oils are higher than fast-pyrolysis oils [23,47].…”
Section: Product Compositionsmentioning
confidence: 99%
“…Thermocatalytic reforming (TCR) is a technology that combines intermediate pyrolysis and high-temperature reforming of volatiles in a single processing system. The organic vapors undergo cracking and reforming, and this results in bio-oil with improved physicochemical characteristics [22,23].…”
Section: Introductionmentioning
confidence: 99%